Fairy tales for Mr. Barker - Ahlberg, Jessica (Somerville, Massachusetts : Candlewick Press, 2016)
While Lucy tries to read to her dog Mr. Barker, he runs off and she ends up chasing him through a fairy tale world where she helps Goldilocks, Jack, the Three Little Pigs, and Sleeping Beauty escape from their enemies.
Keywords: Dogs -- Fiction; Dog owners -- Fiction; Dogs -- Fiction; Fairy tales